De Novo Glioblastoma in the Territory of a Prior Middle Cerebral Artery Infarct - Teresa J. Wojtasiewicz; Andrew F. Ducruet; Sonal S. Noticewala; Peter Canoll; Guy M. McKhann (Case Reports in Neurological Medicine)
We report a case of a patient who developed glioblastoma in the territory of a previous infarction. Two years after an ischemic stroke, the patient presented with a cystic, necrotic, and heterogeneously enhancing mass. Open biopsy and debulking of the mass with histological analysis revealed the mass to be glioblastoma. Though several cases of posttraumatic GBM have been reported, this is the first proposed case of GBM after an ischemic stroke. From this case, we suggest that the ischemic stroke, like other forms of cortical injury, may predispose to glioblastoma formation.